Avaliação in vitro da atividade de antimicrobianos na cavidade bucal sobre Candida glabrata sensíveis e resistentes ao fluconazol - Moreira, Octávio Couto (2016)
Oropharyngeal candidiasis is a challenging fungal disease in the clinical setting of immunocompromised patients, either by their morbidity or by its difficulties in treatment. Patients with AIDS, cancer, and transplanted are among the more affected. Traditionally C. albicans is the main agent of the oropharyngeal candidoasis, but other species such as C. glabrata and C. dubliniensis often show the emergence of resistance phenomenon, especially to azole antifungals agents such as fluconazole. The antiseptic mouthwashes as well as antifungal polyene nystatin, have been recommended as auxiliary agents in reducing the bacterial and fungal load of these patients, contributing to ensure the success of antifungal therapy instituted. In the present study we evaluated the susceptibility of 30 isolates of C. glabrata sensitive to fluconazole and 30 isolates of this species, but resistant to fluconazole against the antiseptic cetylpyridinium chloride, triclosan, chlorhexidine and antifungal polyene nystatin. Assays were carried out through microdilution tests according to the methodology described in document M27-A3 (CLSI, 2008). Comparisons of minimum inhibitory concentrations (MICs) between sensitive and resistant isolates to fluconazole did not show significant differences in susceptibility. On the other hand when it was evaluated the fungicidal activity assays, the minimum fungicidal concentrations (MFCs) showed no significant differences among the CFMs for the cetylpyridinium chloride, triclosan and nystatin. However, to chlorhexidine, the group of yeast resistant to fluconazole was significantly more sensitive to the fungicidal concentrations of antiseptic than fluconazole-sensitive group. The authors discuss these findings, proposing that new approaches must be taken, especially involving isolates of C. glabrata resistant to echinocandins and C. glabrata ability to develop resistance to antiseptics own. Studies evolving C. glabrata biofilms should also be assessed.